2013
DOI: 10.1111/bjd.12162
|View full text |Cite
|
Sign up to set email alerts
|

Provoking factors, including chemicals, in Dutch patients with vitiligo

Abstract: The majority of the patients with vitiligo from this study did not mention provoking factors, but the ones who did point to emotional stress in more than half of the cases. Of the 29 patients who assigned chemical provoking factors, solvents were mainly indicated. However, a presumed relationship with the chemical could be corroborated in only four patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
0
29
1
Order By: Relevance
“…Recently, provoking factors of vitiligo have been reported by using a questionnaire similar to that used in our study21; the subjects reported that emotional stress (55.4%) was the most frequent provoking factor, followed by sunburn (28.8%), mechanical factors (19.2%), and chemical factors (16.4%). However, the overall rate of vitiligo patients who mentioned provoking factors were lower in the present study than in Vrijman et al's21 study, and the prevalence of particular aggravation factors reported by enrolled patients with vitiligo was different, although the items associated with the aggravation of the disease were similar.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Recently, provoking factors of vitiligo have been reported by using a questionnaire similar to that used in our study21; the subjects reported that emotional stress (55.4%) was the most frequent provoking factor, followed by sunburn (28.8%), mechanical factors (19.2%), and chemical factors (16.4%). However, the overall rate of vitiligo patients who mentioned provoking factors were lower in the present study than in Vrijman et al's21 study, and the prevalence of particular aggravation factors reported by enrolled patients with vitiligo was different, although the items associated with the aggravation of the disease were similar.…”
Section: Discussionmentioning
confidence: 82%
“…Therefore, prevention through the early detection of risk factors could be considered more important in vitiligo than treatment itself. Although the aggravating factors of vitiligo have been noted in many reports, only a few studies have analyzed these factors in both the daily life and occupational settings8,21. The purpose of this study was to identify the risk factors and associated aggravating factors of vitiligo in the working environment and in daily life.…”
Section: Discussionmentioning
confidence: 98%
“…(Vrijman et al, 2013) Interestingly, in another study, psychological stress was found to increase the level of neuroendocrine hormones with an impact on the immune system. (Al'Abadie et al, 1994) Therefore, one plausible hypothesis is that this increase in neuroendocrine hormones might be the initiating event in the pathogenesis of vitiligo.…”
Section: Discussionmentioning
confidence: 97%
“…However, due to the needs of the patient and the risk of retraumatization, it is decided against biopsy. Vitiligo might be a result of emotional stress, physical-chemical traumas and burning [26][27][28][29]. Since the lesion emerged after electrical torture, and there is no similar lesion on any part of the body the cable which was wound around penis during electric shock could also be considered to touch his scrotum and cause a burn mark and might be followed by loss of pigment cells.…”
Section: Discussionmentioning
confidence: 99%